2009
DOI: 10.1080/00918360903054210
|View full text |Cite
|
Sign up to set email alerts
|

The Boy Who Would Be Queen: Hints and Closets on Children's Television

Abstract: Although American television programs targeted at children and adolescents posit universal heterosexuality and never openly allude to LGBT persons, a content analysis of 102 episodes of 25 contemporary children's programs revealed many examples of resistance to the heteronormative ideology: intimate same-sex friendships; inclusive statements or stage business; scenes that hint at the existence of same-sex desire; gender-transgressive or otherwise gay-stereotyped characters; and jokes and references that requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…According to this account, because the defining features of gay/lesbian group membership (e.g., gay/lesbian identity, same-sex attraction) are not highly visible, gay and lesbian stereotypes developed—and persist—in culture specifically to create a set of highly visible cues that make it seem that these social groups are visibly identifiable. This function is readily apparent in the media, which has a history of using stereotypic cues to imply that a character is gay or lesbian (Cartei & Reby, 2012; Dennis, 2009; Russo, 1987). Indeed, an abundance of self-report, correlational, and experimental evidence has shown that people rely on stereotypic attributes, such as fashion, hairstyle, or femininity/masculinity, to make judgments about orientation (self-report: Matthews & Hill, 2011; Shelp, 2002; correlational: Ambady, Hallahan, & Conner, 1999; Freeman, Johnson, Ambady, & Rule, 2010, Studies 2 & 3; Gaudio, 1994; Johnson, Gill, Reichman, & Tassinary, 2007, Study 3; Rieger et al, 2010; Smyth, Jacobs, & Rogers, 2003; Van Borsel, & Van de Putte, 2014; experimental: Cox & Devine, 2014; Dotsch et al, 2011, Study 3; Freeman et al, 2010, Study 1; Johnson et al, 2007, Studies 1 & 2).…”
Section: Inferences About Sexual Orientation: the Role Of Stereotypesmentioning
confidence: 99%
“…According to this account, because the defining features of gay/lesbian group membership (e.g., gay/lesbian identity, same-sex attraction) are not highly visible, gay and lesbian stereotypes developed—and persist—in culture specifically to create a set of highly visible cues that make it seem that these social groups are visibly identifiable. This function is readily apparent in the media, which has a history of using stereotypic cues to imply that a character is gay or lesbian (Cartei & Reby, 2012; Dennis, 2009; Russo, 1987). Indeed, an abundance of self-report, correlational, and experimental evidence has shown that people rely on stereotypic attributes, such as fashion, hairstyle, or femininity/masculinity, to make judgments about orientation (self-report: Matthews & Hill, 2011; Shelp, 2002; correlational: Ambady, Hallahan, & Conner, 1999; Freeman, Johnson, Ambady, & Rule, 2010, Studies 2 & 3; Gaudio, 1994; Johnson, Gill, Reichman, & Tassinary, 2007, Study 3; Rieger et al, 2010; Smyth, Jacobs, & Rogers, 2003; Van Borsel, & Van de Putte, 2014; experimental: Cox & Devine, 2014; Dotsch et al, 2011, Study 3; Freeman et al, 2010, Study 1; Johnson et al, 2007, Studies 1 & 2).…”
Section: Inferences About Sexual Orientation: the Role Of Stereotypesmentioning
confidence: 99%
“…In another article, the author demonstrated that sometimes gay allusions are embedded in the texts themselves. Through his content analysis of shows on children's television networks, Dennis (2009) argued that in an hour of evening programming, there will be a dozen hints and signals, references that make no sense without an awareness of gay culture, jokes that subtly acknowledge same-sex desire or practice, intimate friendships that would be instantly ravaged by watchdog groups if they used the word "gay," and exhortations that "nobody can tell you who to love." (p. 739) For the particularly savvy, gender-atypical child who will one day identify as gay, these depictions perhaps present some reassurance.…”
Section: Gender-creative Children On Televisionmentioning
confidence: 99%
“…While children's television has been found to universally uphold mainstream heterosexuality without openly alluding to the concept of homosexuality, there have been instances of resistance to heteronormativity. Within the genre of children's television, it has been found that queer visibility does not match up with images that are made available on mainstream television for adults (Dennis, 2009). This is increasingly problematic as it aligns with the thinking that queer identity is something that children should be sheltered from or, worse, that it is actually exposure to other queers that creates that identity and not a standard life process.…”
Section: Queering Childhoodmentioning
confidence: 99%
“…Hints are also common in animated series, particularly those with fantasy elements, but heterosexuality is still dominant and at the forefront. Live action and animated programs will sometimes have queer stereotypes as drama or gym teachers, however non-child or adolescent characters are consistently portrayed with stereotyped mannerisms while never being openly acknowledged as queer (Dennis, 2009).…”
Section: Queering Childhoodmentioning
confidence: 99%
See 1 more Smart Citation